TANGGUNG JAWAB NOTARIS TERHADAP AKAD MURABAHAH YANG DIUBAH SECARA SEPIHAK DAN MENGAKIBATKAN KERUGIAN BAGI SALAH SATU PIHAK. - Yudistira, Muhammad; Yuhelson, Yuhelson; Kencanawati, Erny (SENTRI: Jurnal Riset Ilmiah, 2023)
In this study, the author found several cases related to the murabahah contract problem which was changed unilaterally by a notary, causing harm to one of the parties. The first formulation of the problem in this study was what was the notary's responsibility for the changes he made to the murabahah contract which was detrimental to the customer? The writer used the theory of legal responsibility according to Abdulkadir Muhammad and the theory of legal protection according to Philip M. Hadjon in order to analyze the problem. This research used normative juridical method and carried out a case approach, a statute approach, and an analytical approach in relation to the problems studied. The legal materials used are primary legal materials and secondary legal material. The researcher carried out data analysis with systematic interpretation. The results of research on usufructuary rights on individual land cannot be encumbered with mortgage rights, this makes it ambiguous between the UUHT and PP 18 of 2021. There needs to be an affirmation in PP 18 of 2021 as well as the guarantee of usufructuary rights so that they can be in line with UUHT. The results of this study indicate that firstly, if the notary is not careful in issuing a copy of the murabahah contract without paying attention to the original offering letter and minutes of the murabahah contract which has been agreed upon by the parties so as to cause a change in the clause in the murabahah contract which causes losses to the customer, the notary can be held accountable in a civil manner according to Article 1365 of the Civil Code in the form of a claim for compensation in the case of committing an unlawful act this is in accordance with the theory of responsibility due to unlawful acts committed due to negligence (negligence tort lilability) according to abdulkadir muhammad. Secondly customers are protected by the existence of repressive legal protection, namely dispute resolution through litigation in religious court institutions in protecting rights that are violated in murabahah contracts, especially in sharia economic disputes, this is in accordance with the provisions of Article 55 paragraph (1) of Law 21 of 2008 concerning Banking. This sharia is in line with the theory of repressive legal protection according to Philip M. Hadjon.